Effect of Managerial Ownership Structure, Leverage, and Firm Size on Accounting Conservatism: Pengaruh Struktur Kepemilikan Manajerial, Leverage, dan Ukuran Perusahaan Terhadap Konservatisme Akuntansi - Febrianto, Albiansa; Nurasik, Nurasik (Indonesian Journal of Law and Economics Review, 2018)
This research was conducted to analyze the effect of Managerial Ownership with Accounting Conservatism at Mining companies listed on BEI period 2014-2016; analyze the effect of Leverage with Accounting Conservatism on Mining companies listed on the IDX for the periode2014-2016; as well as analyzing the effect of Company Size with Accounting Conservatism on Mining companies listed on BEI period 2014-2016; This research is a type of quantitative research, with the overall population of mining companies listed on the Stock Exchange in the 2014-2016 period with a total of 39 companies. Determination of the sample was done by purposive sampling method and obtained sample of 18 companies. The analytical tool used is classical assumption analysis, multiple linear regression coefficient, determination coefficient, t test and F test using SPSS version 20 for windows. The result of the research shows that managerial ownership variables significantly influence accounting conservatism variables in mining companies listed in BEI period 2014-2016; leverage variables significantly influence the variables of accounting conservatism in mining companies listed on the BEI period 2014-2016; and firm size variables significantly influence the variables of accounting conservatism in mining companies listed on the BEI period 2014-2016.